E-LEARNING IMPLEMENTATION IN THE POST COVID-19 PANDEMIC: LECTURERS’ AND STUDENTS’ PERCEPTION - Syafrizal Syafrizal; Juni Mahsusi; Muhammad Cholid (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Many universities have integrated technology through the utilization of Learning Management System (LMS) into the process of teaching and learning especially in the post Covid-19 Pandemic. Google Classroom is one of the platforms used by the lecturers and students. The purpose of this study is to determine the lecturers' and students’ perception of the implementation of online learning using Google Classroom in the Post Covid-19 pandemic. The subjects of the research were the lecturers and students of English Education Program of University of Indragiri. There were 15 lecturers and 62 students involved in this study. They were selected using the purposive sampling technique. The researcher collected the data through questionnaires adapted from Harjanto (2019) and Afriani (2021) and then the data were classified based on the indicators. Descriptive quantitative design was applied in this study. In general, the results revealed that the lecturers and students had positive perception in using Google Classroom in post Covid Pandemic.